SISTEM PENGOLAHAN LIMBAH GAS CIANIDA PADA INDUSTRI PESTISIDA STUDI KASUS PT. ALFA ABADI PESTISIDA - JAWA BARAT - Supriyo, Edy (METANA, 2007)
Abstract   Pesticide industries produce substance to kill pest and weeds, therefore product,side product, raw  material and its wastes are hazardous and poison. The main pollution from pesticides industries are air pollutant. According to property of the wastes, treatment wastes include combination of absorbtion, catalytic and condensation order to match with limiting value by government. After being treated, the component moritored i.e. CN was reduced from 10 mg/lt become 0.01 mg/lt   Keywords : cyanide, pesticide industry.